UPAYA MENINGKATKAN LITERASI DENGAN MEDIA PUZZLE BERBASIS LITERASI DALAM KEGIATAN PEMBELAJARAN - Nufus, Ajijah Sadiah (Early Stage, 2024)
The research aims to increase literacy learning in the classroom by using puzzle media. The researchers used the classroom action research method with the. Kemmis and MC Teggart models with two cycles and through 4 stages: 1) planning, (2) action, (3) observation, and (4) reflection. The data collection technique in this study is qualitative data with observations, interviews, and documentation. In addition to the qualitative analysis of the study, the first stage of the researchers carried out re-observation with the result of the child's learning rate in the class is 27.50%, After carrying out the re-observance researchers designed learning activities using literacy-based puzzle media. At cycle, I, the child’s learning literacy began to increase to 52.50% followed by the second cycle and there was a further increase of 95%. So it can be stated media puzzles can enhance literacy education.